Neuropsychiatric systemic lupus erythematosus - Kiki Mohammad Iqbal (Majalah Kedokteran Nusantara The Journal Of Medical School, 2012)
Systemic lupus erythematosus (SLE) is a chronic, heterogenous, autoimmun disease with diverse clinical manifestations, which can include end-organ damage. Neuropsychiatric systemic lupus erythematosus (NP-SLE) is defined as abnormalities of the central, peripheral and autonomic nervous systems and the psychiatric syndromes observed in patients with SLE for which other causes have been excluded.. However, the pathogenic mechanisms that result in primary neuropsychiatric manifestations in NP-SLE are throught to include autoantibodies, vascular abnormalities, and the local production of inflammatory mediators. Diagnosis is typically achieved throught careful analysis of clinical, laboatory, and imaging data on a case-by-case basis. A better approach to management of NP-SLE may be achieved by : 1) the recognition of the antiphospholipid syndrome and its treatment with anticoagulants; 2) the use of steroids, especially in patients with mild manifestations; and 3) the use of pulse cyclophosphamide in diffuse / nonthrombotic CNS lupus.Keywords : neuropsychiatric; systemic lupus erythematosus